Seasonal lake‐to‐air temperature transfer functions derived from an analysis of 1395 modern lakes: A tool for reconstructing air temperature from proxy‐derived lake water temperature - Alexa Terrazas; Nathan Hwangbo; Alexandrea J. Arnold; Robert N. Ulrich; Aradhna Tripati (The Depositional Record)
Abstract Lacustrine palaeotemperature reconstructions are important for characterising past temperature and hydroclimate change, validating multi‐proxy reconstructions and evaluating global climate models. In particular, lake water temperature is often derived from geochemical proxies—including clumped isotopes (Δ47), oxygen isotopes (δ18O), alkenone lipids (Uk’37) and GDGT compounds (TEX86). However, global climate models, constrained by resolution, computational demand and cost, are designed to simulate large‐scale processes, often at the expense of resolving lakes and simulating lake temperature. Consequently, this limitation complicates the comparison of climate model‐simulated variables such as air temperature, with lake water temperature or with other proxy variables (e.g. pollen‐derived air temperature), and requires the use of a transfer function to relate lake temperature to air temperature. Previous work developed transfer functions to translate proxy‐derived seasonal lake water temperature to mean annual air temperature using ground‐based measurements from 88 lakes. This study reports new lake‐to‐air temperature transfer functions (for annual, spring through summer, spring, summer and warmest month) that incorporate lake surface water temperature, and new variables including latitude and elevation, by analysing climate reanalysis data and long‐term satellite observations of surface temperatures for 1395 modern lakes via regression‐based inverse modelling. With the use of multiple regression models and a dataset roughly 10 times larger, the error in predictions of mean annual air temperature is reduced by up to 48% compared to previous work. To demonstrate the potential of the new transfer functions for integrating and comparing proxy data with model output, Pliocene and Pleistocene mean annual air temperature was reconstructed from Δ47‐derived lake temperatures and compared with model simulations for the Last Glacial Maximum and mid‐Piacenzian warm period. The new transfer functions, with reduced error, should enable more accurate palaeotemperature reconstructions from proxy‐derived lake water temperature and allow for more comprehensive assessments of climate model skill.